Toughening of polyamide 6 nanocomposites: effect of organoclay and maleic anhydride grafted polyethylene octene loading on morphology and mechanical properties - Wahit, Mat Uzir (University of Malaya, 2009)
Rubber toughened nanocomposites consisting of ternary blends of polyamide 6 (PA 6), maleic anhydride grafted polyethylene octene (POEgMAH) and organically modified montmorillonite (organoclay) were prepared by melt compounding followed by injection moulding. The mechanical properties and morphology of a series of PA 6/organoclay/POEgMAH ternary nanocomposites with different compositions of organoclay and POEgMAH was investigated. Mechanical properties were studied through tensile, flexural and impact properties. Scanning electron microscope (SEM) and X-ray diffraction (XRD) were used to examine the morphology of the nanocomposties. The results showed that the combined incorporation of the organoclay and POEgMAH as into PA6 matrix has led to ternary compounds where both the reinforcing effect of the organoclay and the toughening effect of the elastomer were observed. X-ray diffraction analysis (XRD) revealed that an intercalated organoclay silicate layer structure was formed in rubber-toughened PA6 nanocomposites. SEM study revealed a two-phase morphology where POE, as droplets was finely and uniformly dispersed in the PA6 matrix.